Сценарний підхід у прогнозуванні податкових надходжень державного бюджету України - Martynenko, Valentyna (Dr. Viktor Koval, 2019)
Introduction. State revenue management stands first in the areas of government regulation, which is provided by the regulation of fiscal policy. It is achieved by optimizing the amount of nationwide taxes and their tax rates, with the least amount of tax evasion. It is also important to ensure the implementation of the budget process, which is based on budget planning and forecasting, the effectiveness criterion of which is the reliability of the forecast. The compulsory component of extrapolation of time series – the most used forecasting method – is the scenario approach, so the research of possibilities of its implementation is relevant. Aim and tasks. The aim of the article is to introduce a scenario approach in forecasting tax revenues of the state budget of Ukraine. The main tasks set to achieve this aim are: modeling the dependence of tax revenues on macroeconomic indicators; trend analysis and extrapolation of time series of macroeconomic indicators; development of forecast scenarios of state budget revenues from state taxes. Results. It is proved that comprehensive stimulation of the production of gross value added, especially in the sphere of material production, as a basis for economic growth, will have a positive impact on the growth of output of goods and services, as well as will provide an increase in the revenues from value added tax (VAT) and excise tax to the state budget. Provision at the state level of further growth of the minimum wage and the deployment of social programs, as well as stimulating the legalization of shadow incomes of individuals in order to stimulate incomes of the population will lead to revenue increase from the personal income tax to the state budget. Creating favorable conditions for doing business by creating a business environment free from corruption, legalizing the shadow income of legal entities in order to maximize the profit of gross profit, mixed income will lead to an increase in corporate income tax revenues and subsoil use fee to the state budget of Ukraine. Conclusions. Over the next 5 years, aggregate tax revenues to the state budget will increase, regardless of the forecast scenario. The largest contribution to tax revenue growth can be provided by excise tax. The dynamics of the remaining taxes will also be increasing. Because the extrapolation of time series and scenario analysis are applied and universal methods of forecasting, they can be used in forecasting tax revenues of both consolidated and local budgets of Ukraine. Prospects for further research of the author will be relevant to these areas.